2007
DOI: 10.1108/13612020710751365
|View full text |Cite
|
Sign up to set email alerts
|

Cohort perception of luxury goods and services

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 14 publications
0
30
0
1
Order By: Relevance
“…However, the results provide evidence of differences in the evaluations of these dimensions among nationalities, especially between Eastern and Western cultures (Li & Su, ; Podoshen, Li, & Zhang, ; Shukla, ; Tsai, ). Nevertheless, as revealed by Dubois and Laurent () and Dubois, Laurent, and Czellar () and emphasized by several national studies (e.g., Hauck & Stanforth, ; Tervydyté & Janciauskas, ), the relevance of the four dimensions may also vary within countries but are similar among cross‐cultural segments. Therefore, this study aims to identify whether consumers in different parts of the world buy or wish to buy luxury products for varying reasons; whether they possess similar values; and, regardless of their country of origin, whether their basic motivational drivers may be similar with respect to the financial, functional, personal, and social dimensions of luxury value perceptions, although the relative importance of the different dimensions varies.…”
Section: Conceptualizationmentioning
confidence: 98%
“…However, the results provide evidence of differences in the evaluations of these dimensions among nationalities, especially between Eastern and Western cultures (Li & Su, ; Podoshen, Li, & Zhang, ; Shukla, ; Tsai, ). Nevertheless, as revealed by Dubois and Laurent () and Dubois, Laurent, and Czellar () and emphasized by several national studies (e.g., Hauck & Stanforth, ; Tervydyté & Janciauskas, ), the relevance of the four dimensions may also vary within countries but are similar among cross‐cultural segments. Therefore, this study aims to identify whether consumers in different parts of the world buy or wish to buy luxury products for varying reasons; whether they possess similar values; and, regardless of their country of origin, whether their basic motivational drivers may be similar with respect to the financial, functional, personal, and social dimensions of luxury value perceptions, although the relative importance of the different dimensions varies.…”
Section: Conceptualizationmentioning
confidence: 98%
“…The term luxury good, although used in everyday life, is a difficult concept to define, as perceptions of luxury differ according to the consumer's lifestyle (Hauck and Stanforth 2007) and even change depending on an individual's mood (Nia and Zaichhkowsky 2000). A common definition of what constitutes luxury is therefore lacking in the literature (Vickers and Renand 2003).…”
Section: Research Errormentioning
confidence: 99%
“…Another study discussed the age impact in regard to luxury goods and services [11], using three different age categories, less than 25 years, 25 to 50 years and more than 50 years old. Actually, results showed that the age perception of a luxury good or service is depending on the type of luxury product.…”
Section: B Young Luxury E-consumer Profilesmentioning
confidence: 99%